A terminological issue: Islamic philosophy or philosophy in the Islamic world? - Moris, Megawati (2020)
There have been debates and contentions on what should be the name, translated into English language, given to the discipline falsafah or ḥikmah in the Islamic intellectual tradition. Some of the common names given to it by both Western and Muslim scholars are Islamic Philosophy, Muslim Philosophy and Arabic Philosophy. More recently the term “Philosophy in the Islamic World” was made popular by the scholar and philosopher Peter Adamson of LMU Munich. The reason for using this term which Adamson considers as a terminological issue is that it is the “most appropriate”, and the name Islamic Philosophy is “too obvious”. . Using and explaining the correct term would help to clarify how Islamic philosophy is essentially Islamic in its worldview, philosophical foundations, objectives, characteristics and method. This counters the common misunderstanding that Islam does not have an authentic philosophical tradition of its own. Understanding the real meaning and role of Islamic philosophy is important to avoid the commonly held view by Muslims and non-Muslims alike that Islam has an anti-intellectual and irrational stance. Implication: Muslims resort to emotions and violence which is the cause of its extremism.